Increasing the yield attributing character of different species of Pleurotus through hybridization - Riba, Karishmi; Sarmah, D K (Mushroom Research, 2021)
Interspecific hybridization studies were carried out between Pleurotus sajor-caju, P. sapidus and P.flabellatus for obtaining better quality strains. Out of 48 crosses, only five inter specific crosses of P. sajor-caju x P. sapidus and four inters specific crosses of P. sajor-caju x P. flabellatus were compatible. Inter specific crossing between P. sapidus and P. flabellatus failed to show any compatible reaction. The compatible crosses were tested for evaluating their growth characteristics on MEA media and the cross SC2S1 have shown significantly higher mycelial growth rate (8.89 cm) which was followed by the cross SC1S1 (8.66 cm). The obtained hybrid crosses have shown denser and regular growth with floccose, cottony and aerial mycelial texture and also showed off-white, pure white and yellowish white in colony colour. Out of nine dikaryotic strains, the cross SC2S1 (P. sajor-caju x P. sapidus) was the best strain among all the obtained hybrid strains and its parental strains interms of number of days required for spawn run (11.50 days), number of days required for pin head formation (15.50 days), days required for harvesting (18.50 days), total number of fruiting body (214.00), weight of the individual fruiting body (20.00 g), total yield per bag (0.95 kg) and biological efficiency (95.00%). Whereas in terms of stipe diameter, the cross SC2F2 (P. sajor-caju x P.flabellatus) has shown maximum stipe diameter (3.50 cm) as compared to other dikaryotic strain and its parental strain and among the dikaryotic strain the cross SC1S2 (P. sajor-caju x P. sapidus) have shown significantly higher stipe length (6.41 cm), which was also higher than their respected parents. Maximum cap size (6.73 cm) was recorded in the cross SC1F2 (P. sajor-caju x P. flabellatus) which was significantly higher than the other dikaryotic strain and its parental strain. During sensory evaluations, the product B (P. sajor-caju x P. flabellatus) was rated better than the global mean in overall acceptance (8.56), taste (8.90), flavour (7.90), colour (7.40) and appearance (8.13), with highest score in all the sensory parameters followed by Product A (P. sajor-caju x P. sapidus). While the lowest score was obtained by P. sapidus (product D) followed by P. flabellatus (product E) and P. sajorcaju (product C).